Supernatural in Malay people folklore in the Langkawi, Kedah district - Halim, Nor Hanisah; Abu Bakar, Roslina; Sujud, Arba'ie (Human Resource Management Academic Research Society, 2021)
The tradition of the Malay believes in supernatural elements in all aspects of life such as in matters that involves beliefs towards the existence of the unseen. According to Noriah (1983), supernatural incidents are matters that cannot be grasped by the normal ability of the human being such as the existence of the other unseen creations, spiritual creatures that in reality cannot be assumed but its existence is convinced by the affects towards humans. Apart from that, the existence of universal objects that are out of the ordinary with ferocious or out of the ordinary animals, natural phenomenon that are considered out of the ordinary and all the out of the ordinary attributes cannot be explained by the rational thinking of the people. According to Roslina (2012) the Malay folklore is not only of the literary sayings to the public but can give a picture of a lifestyle or cultural circumference of a people, but folklore is able to depict a picture of human relationship with magic. Therefore, this study is done to recognize and analyse supernatural elements in Malay folklore in the Langkawi, Kedah district. This study applies the R. LINA: two-way planned communication (R.L.: KDHT) model. This study uses the field method and content analysis. The data of this study includes the stories of Puteri Dayang Bunting and Mahsuri. The outcomes of the study finds that Malays folklore in the Langkawi, Kedah district has natural phenomenon supernatural elements that are out of the ordinary and supernatural objects that is still believed to be true by the local public towards its existence even the belief towards supernatural powers that are influenced by animism and Hindu beliefs has long been abandoned by the Malay public tradition.